FINANCIAL CRISIS IN INDIA: IN THE ERA OF COVID 19 - Dr. Sadhana Gupta, Mr. Shikhar Saxena, Mrs. Rita Singh (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Financial inclusion plays the very important role in the growth of any country. In India, the role of government is always on the growth and development by the financial inclusions for this they launched various schemes. Every sector, industry, financials, and daily life has been suffered a lot due the COVID 19. However, to protect the lives government took severe action such as complete lockdown but somewhere it has also affected the financial inclusions schemes and procedures. In this study we use secondary data to analyse the role of financial inclusion in the era of COVID 19. We conclude with the statement that small businesses, financial institutions and daily earners may take many days to recover their losses and also occurs extra cost to get the adequate lifestyle.